2021
DOI: 10.1002/jrs.6089
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy in the detection of adulterated essential oils: The case of nonvolatile adulterants

Abstract: Essential oils are liquid mixtures of volatile compounds extracted from plants. Their quality is usually controlled via gas chromatography (GC), although with limitations when adulterants are nonvolatile substances. The essential oils of lavender (Lavandula angustifolia Mill.), peppermint (Mentha piperita L.), patchouli (Pogostemon cablin Benth), and their adulterated versions were measured by GC coupled to flame ionization detector (GC‐FID) and Raman spectroscopy. Canola oil, a nonvolatile substance, was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…It is worth mentioning that the simple determination of physico-chemical characteristics of the extracts may not be enough for evaluating some adulterations, and the use of more powerful analytical techniques may be required, e.g., gas and liquid chromatography, mass spectrometry, magnetic nuclear resonance, raman spectroscopy or infrared spectroscopy [83][84][85][86][87]. Figure 2 summarized the different steps for characterization of the purity of essential oils together with the advantages and disadvantages associated with the different analytical methodologies.…”
Section: Quality Of Eosmentioning
confidence: 99%
“…It is worth mentioning that the simple determination of physico-chemical characteristics of the extracts may not be enough for evaluating some adulterations, and the use of more powerful analytical techniques may be required, e.g., gas and liquid chromatography, mass spectrometry, magnetic nuclear resonance, raman spectroscopy or infrared spectroscopy [83][84][85][86][87]. Figure 2 summarized the different steps for characterization of the purity of essential oils together with the advantages and disadvantages associated with the different analytical methodologies.…”
Section: Quality Of Eosmentioning
confidence: 99%
“…These results indicated that this method, when combined with PCA, can visually distinguish pure and adulterated camellia oils in the vast majority of cases. Adulteration in any percentage can be held liable, but low amounts of adulteration are intended only for bulk substances to increase the volume (or weight) of the product, and adulteration of less than 5% (v/v) is of a worthless nature (Vargas Jentzsch et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Due to increased demands and insufficient regulation, the adulteration of essential oils became a common practice along supply chains, generating safety concerns in the EOs industry [56]. The EOs adulteration could be performed using various methods: a cheaper oil addition [57] to the original one (e.g., corn mint to Peppermint oil), EOs' dilution with vegetable oils, and synthetic phytochemicals' inclusion [51] in the original EO [58][59][60]. Thus, supplementary quality control measures should be taken to ensure safety for human use [61,62].…”
Section: Discussionmentioning
confidence: 99%